Aggregate earnings surprises, monetary policy, and stock returns - GALLAO, Lindsey A. (Institutional Knowledge at Singapore Management University, 2016)
This paper examines whether the negative association between aggregate earnings and returns is explained by the monetary policy news in aggregate earnings. Using Federal funds futures data to construct a measure of policy news, we find that aggregate earnings convey information about the Fed׳s policy actions. Additionally, the negative aggregate earnings-returns association is muted when we control for policy surprises. This result is more pronounced in periods with negative policy surprises, which tend to trigger a more significant market reaction. Taken together, these results suggest that aggregate earnings convey policy news and the market reacts negatively to policy surprises, which drives the negative aggregate earnings-returns association.